Enforced hamiltonian cycles in generalized dodecahedra - Maria Timkova (Electronic Journal of Graph Theory and Applications (EJGTA), 2013)
The H-force number of a hamiltonian graph G is the smallest number k with the property that there exists a set W ⊆ V (G) with |W| = k such that each cycle passing through all vertices of W is a hamiltonian cycle. In this paper, we determine the H-force numbers of generalized dodecahedra.